2006
DOI: 10.1097/01.cad.0000215059.93437.89
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of treosulfan and busulfan on pediatric tumor cell lines

Abstract: High-dose chemotherapy of solid tumors aims at eliminating residual or metastatic tumor cells, which remained after conventional treatment. Thus, anticancer drugs used for high-dose chemotherapy should display significant cytotoxicity against the respective tumors. As little data are available about the in-vitro toxicity of busulfan and treosulfan especially on pediatric tumor cell lines, we compared the cytotoxicity of treosulfan and busulfan on four Ewing tumor, four neuroblastoma, two osteosarcoma and two l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
0
10
1
2
Order By: Relevance
“…The concentrations of busulfan fall within the concentration ranges recently used by Lanvers-Kaminsky et al (2006) who found a great variation in cellular susceptibility to this anticancer drug. For example, while growth of leukemia cell lines was inhibited by micromolar concentrations, millimolar concentrations were required to inhibit growth of osteosarcoma cell lines.…”
Section: Resultsmentioning
confidence: 58%
“…The concentrations of busulfan fall within the concentration ranges recently used by Lanvers-Kaminsky et al (2006) who found a great variation in cellular susceptibility to this anticancer drug. For example, while growth of leukemia cell lines was inhibited by micromolar concentrations, millimolar concentrations were required to inhibit growth of osteosarcoma cell lines.…”
Section: Resultsmentioning
confidence: 58%
“…It was found to have therapeutic effects in various in vitro and in vivo models of AML, ALL and multiple myeloma (MM). [17][18][19][20][21] It reduced the viability of human myeloid leukemia cells, even at low concentrations of 10 and 30 mm, by more than 70 and 90%, respectively. 22 Although it is inadequate to correlate in vitro data with plasma levels and response rates in vivo, it is notable that in the in vitro experiments, the concentrations needed to eliminate more than 90% of the leukemia cells were in the range of 100 mM; concentrations that are 10-fold lower than the plasma levels achievable in patients given conventional doses (1 mmol/L).…”
Section: Treosulfan: Clinical Pharmacologymentioning
confidence: 99%
“…It demonstrates cytotoxic/antiproliferative activity against a wide range of hematological malignancies and solid tumors, including important childhood malignancies. [9][10][11][12][13] In addition, TREO reveals an excellent hematopoietic stem cell toxicity and immunosuppressive effects, which are even superior to those of BU. 14,15 As shown in adults, an additional advantage of TREO lies also in its predictable linear pharmacokinetics over a broad i.v.…”
Section: Introductionmentioning
confidence: 99%